Comprehensive geohazard detection along the Qinghai-Tibet Plateau transportation corridor based on multi-sourced earth observations - Zhenhong Li; Chenglong Zhang; Chen Yu; Mingtao Ding; Wu Zhu; Trevor B. Hoey; Bo Chen; Jiantao Du; Xinlong Li; Jianbing Peng (International Journal of Applied Earth Observations and Geoinformation)
Geohazards are sudden and catastrophic. Due to the complicated topography, geology and climate conditions along the Qinghai-Tibet Plateau Transportation Corridor (QTPTC), many geohazards pose unprecedented challenges for engineering construction. Comprehensive and scientific geohazard detection has been infrequently performed in the QTPTC, so the study area still lacks a comprehensive geological hazard inventory. With the development of earth observation techniques, detecting geohazards in wide areas is possible. However, comprehensive geohazard detection over such a large spatial extent is considered impossible by individual remote sensing techniques and images. In this study, we used a combination of GACOS-assisted Interferometric Synthetic Aperture Radar (InSAR) phases, SAR amplitudes, and optical images to acquire deformational and geomorphological information of geohazards along the QTPTC. Based on deformational and geomorphological information, we establish a catalogue containing 2109 geohazards which were classified into five categories, i) actively deforming slopes (994); ii) reactivated historically deformed slopes (84); iii) stabilized historically deformed slopes (732); iv) glacier (283) and v) glacial lakes (16). A large percentage of geohazards are distributed at an elevation of 2500–5000 m with slope angles of 30-40°, five geohazards concentration regions are distributed on main active fault zones, and the types of geohazards in the five regions are influenced by precipitation and surface temperature. Finally, three field surveys were also carried out to verify 141 geohazards along the QTPTC. The above findings can improve disaster prevention and mitigation capabilities for construction and operation along the QTPTC.